Czy politologia to „nauka interdyscyplinarna”? Kilka słów o przedmiocie poznania i tożsamości dyscypliny - Karczewski, Maciej (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2013)
The article provides a short and synthetic analysis about condition of political science in Poland. It is a voice in the debate about the subject of cognition in the discipline. The article focuses on the problem of interdisciplinarity in political science. Author argues that the lack of reflection on the subject of discipline knowledge leads to the impoverishment of its achievements.